A identidade, o costume e o direito da decisão: um estudo sobre o uso e o desuso do sobrenome do marido - Giacometti, Fabiana Aparecida Prenhaca [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The woman's right to choose between adding or not the husband's surname was promulgated in 1977. The surname of a person demarcates its identity, it is a right related to human decency. Therefore, the full name is the individualization of the human in the society, being one of the main rights of citizenship. Intangible element, but as fundamental as the set of goods and wealth held by individuals. For a long time for brides, it was a requirement: every woman that formalize her marriage, should add the husband's surname to her family. Today it became a choice and no more an obligation. This qualitative-descriptive research aimed to establish if in the practice the transformation in legislation changed the women habits in add or not the husband surname when marrying. From a questionnaire applied in 20 women who were married legally after the date of the right valance answered questions consisting of open and closed questions based on a guide for programmatic content analysis. The results obtained indicate that for most participants using the surname of her husband it happened in automatic mode (since their grandmothers and mothers carry the surname of their spouses), showing the strength of custom and exclusion toward the male, confirmed through the submission in do it without realizing why. Also discovered that not always the participants of this investigation were informed at City Hall about the possibility of not add the surname's husband to his name. Were not advised of their rights, lacking this education at school and in the family. With this clear lack of knowledge of the Brazilian Civil Code, brings the necessity of do a social work: this research culminates with a proposal of educational intervention that offers the cultural capital missed for the betrothed, because it is necessary to put people knowing the laws and their rights. The intervention is about a drafting of a booklet entitled ...

El derecho que la mujer tiene al elegir entre la adición o no del apellido del marido fue promulgado en 1977. El apellido de una persona delimita su identidad, es un derecho relacionado con la decencia humana, por lo tanto, el nombre completo es la individualización de los seres humanos en la sociedad, siendo uno de los principales derechos de ciudadanía. Por mucho tiempo, para las novias, era un requisito: cada mujer que oficializaba el matrimonio, habría que añadir el apellido del varón a lo apellido de su familia. Hoy se trata de una opción y no es más una obligación. Esta investigación cualitativa descriptiva, tuvo por objetivo de examinar si en la práctica las permutas de la legislación cambiaron demasiado o poco los hábitos de las mujeres al uso del apellido del marido al casarse. Además, delimitar quiénes son las mujeres del presente y cómo han reaccionado a la utilización del derecho vigentes en la Ley. Con un cuestionario, aplicado en 20 mujeres casadas legalmente después de la fecha inicial del derecho que respondieron a las preguntas que constan de indagaciones abiertas y cerradas, basadas en una ruta de cuestiones para el análisis de los contenidos programáticos. Los resultados obtenidos indican que para la mayoría de las participantes el uso del apellido del marido se pasó así de modo Automático (Puesto que sus abuelas y madres llevan el apellido de sus maridos). Demostrando la fuerza de la costumbre y la exclusión ante el hombre, confirmada a través de la subordinación en el cual sin que se dan cuenta la hacen. También constatase en esta investigación que no siempre las participantes de esta investigación fueron informadas sobre la posibilidad de agregar el apellido del marido a su nombre. No fueran aconsejadas de sus derechos, pasó la ausencia de tal educación en la escuela y en la familia. Con esta clara falta de conocimiento sobre el Código ...

O direito da mulher para poder optar entre adicionar ou não o sobrenome do futuro marido foi promulgado em 1977 (art.50 da Lei 6.515/77). O sobrenome de uma pessoa demarca a sua identidade, se trata de um direito relacionado à decência humana, portanto, o nome completo é a individualização do ser humano na sociedade, sendo um dos principais direitos de cidadania. Por muito tempo, para as noivas, tratava-se de uma obrigatoriedade: toda mulher que oficializasse o matrimônio, teria que acrescentar o sobrenome de seu esposo ao de sua família. Hoje, se trata de escolha e não mais de obrigação. Esta pesquisa, de cunho qualitativo-descritivo, teve por objetivo averiguar se na prática as mudanças da legislação (modificações legais ocorridas desde a Lei do Divórcio em 1977 até o Novo Código Civil de 2002) alteraram os hábitos das mulheres em inserir ou não o sobrenome do marido ao casar. A partir de um questionário, aplicado em 20 mulheres que se casaram legalmente após a data da valência desse direito que responderam às questões nas quais consistiam em perguntas abertas e fechadas baseadas em um roteiro para análise do conteúdo programático. Os resultados obtidos indicaram que para a maioria das participantes o uso do sobrenome do marido aconteceu de modo Automático (já que suas avós e mães carregam os sobrenomes de seus esposos), demonstrando a força do costume e a exclusão perante o sexo masculino, confirmada através da submissão na qual sem que percebam a fazem. Também se constatou que nem sempre as participantes dessa investigação foram informadas no cartório sobre a possibilidade de deixar de adicionar o sobrenome do marido ao seu nome. Não foram avisadas sobre os seus direitos, faltou essa educação na escola e na família. Com essa nítida ausência de conhecimento acerca do Código Civil Brasileiro, veio a necessidade do fazer social: a presente pesquisa...
The identity, the usual and the right of decision: a study on the use and disuse of the husband's surname
La identidad, la costumbre y el derecho de la decisión: un estudio sobre el uso y desuso del apellido d el marido
Keywords: Mulheres; Direito; Valores sociais; Casamento; Atitudes; Social values